2014
DOI: 10.1039/c4ob01494d
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial epipolythiodioxopiperazine and unprecedented sesquiterpene from Pseudallescheria boydii, a beetle (coleoptera)-associated fungus

Abstract: Pseudallescheria boydii residing in the gut of coleopteran (Holotrichia parallela) larva produces four new epipolythiodioxopiperazine (ETP) boydines A-D (3-6) and two novel sesquiterpene boydenes A (7) and B (10), in addition to bisdethiobis(methylthio)-deacetylaranotin (1), bisdethiodi(methylthio)-deacetylapoaranotin (2), AM6898 A (8) and ovalicin (9). The structure elucidation was accomplished by a combination of spectral methods with quantum chemical calculations of optical rotations and electronic circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…From the culture filtrates of the fungus Pseudallescheria boydii residing in the gut of a coleopteran ( Holotrichia parallela ) larva, four new epipolythiodioxopiperazines named boydines A–D ( 112 – 115 , Figure 8 ) were isolated together with six other known and new metabolites [ 68 ]. All the isolated fungal metabolites were assayed for in vitro antibacterial activity against pathogenic anaerobes isolated from clinical specimens.…”
Section: Structure–activity Relationship Studies Performed With Fumentioning
confidence: 99%
See 1 more Smart Citation
“…From the culture filtrates of the fungus Pseudallescheria boydii residing in the gut of a coleopteran ( Holotrichia parallela ) larva, four new epipolythiodioxopiperazines named boydines A–D ( 112 – 115 , Figure 8 ) were isolated together with six other known and new metabolites [ 68 ]. All the isolated fungal metabolites were assayed for in vitro antibacterial activity against pathogenic anaerobes isolated from clinical specimens.…”
Section: Structure–activity Relationship Studies Performed With Fumentioning
confidence: 99%
“…Only boydine B ( 113 ) showed a strong inhibition against Peptostreptococcus sp., Bifidobacterium sp., Anaerostreptococcus sp., and Veillonella parvula with a MIC range of 0.2–0.8 μM. The SAR study on the cyclic dipeptides suggested that the antibacterial activity might be dependent on the combination of the acyl residue with a diketopiperazine nucleus condensed from two (2 R ,7 S ,7a S )-7-hydroxy-2-(methylthio)-2,3,7,7a-tetrahydro-1 H indole-2-carboxylic acids [ 68 ].…”
Section: Structure–activity Relationship Studies Performed With Fumentioning
confidence: 99%
“…Additional insights into the dalesconol biosynthesis was gained from a characterization of minor dalesconols and biosynthetic intermediates only present in chemical extracts prepared from a large-scale fermentation. The ascomycete fungus Pseudallescheria boydii , isolated from the gut of the larvae of the beetle Holotrichia parallela , showed also a broad range of bioactive secondary metabolites including epipolythiodioxopiperazines, named boydines (e.g., boydine B, ( 37 )) [ 120 ]. Boydines significantly inhibit clinically relevant anaerobic bacterial strains (e.g., Bifidobacterium sp., Veillonella parvula , Anaerosterptococcus sp., Bacteroides vulgatus , and Peptostreptococcus sp.…”
Section: Reviewmentioning
confidence: 99%
“…The findings of other relevant investigations include: the production of new cytotoxic furanone analogues, paraconfuranones A (9)-H by a fungal strain belonging to Paraconiothyrium brasiliense isolated from the gut of the grasshopper, Acrida cinerea (Liu et al 2015); the production of a series of new epipolythiodioxopiperazines, boydines A (10)-D, and structurally novel sesquiterpenes, boydenes A and B (11) by a symbiotic fungus Pseudallescheria boydii, in the gut of the coleopteran larva of the beetle Holotrichia parallela (boydine B displayed significant inhibitory activity against clinically-relevant bacterial strains Bifidobacterium sp., Veillonella parvula, Anaerosterptococcus sp., Bacteroides vulgatus and Peptostreptococcus sp.) (Wu et al 2014); and the production of a new polyketide glycoside, bionectriol A (12) by a fungal strain belonging to Bionectra sp. associated with the fungus-growing ant (Apterostigma dentigerum) (Freinkman et al 2009).…”
Section: Chemical Biology Of Gut Bacteria and Their Secondary Metabolmentioning
confidence: 99%